Organizational Structure, Governance, Leader Characteristics and Organizational Performance: Case Study of Sinergy Tani and Harapan Gumanti Farmers Group in Gumanti Valley, Solok Regency. - Chandra, Alfi; Games, Donard; Sari, Dessy Kurnia Sari (Business and Investment Review, 2023)
Until now agriculture is still a superior basis for the economy of rural communities. The aims of this research are (1) To determine the role of the organizational structure of farmer groups in the Gumanti Valley. (2) Knowing the role of governance in farmer groups in the Gumanti Valley. (3) knowing the role of leader characteristics in farmer groups in the Gumanti Valley. (4) knowing the role of performance in farmer groups in the Gumanti Valley. The approach used in this research is a qualitative approach. Data obtained through observation techniques, interviews, and documentation. Test the validity of the data by means of data triangulation. Data analysis techniques use comparative or comparative analysis. The results showed that the organizational structure of Sinergy Tani and Harapan Gumanti was clearly arranged according to the division of labor, duties and authority of each organization's management. The management of the Sinergy Tani farmer group is carried out based on the AD ART that has been made. in the Harapan Gumanti farmer group organization also manages organizational management. characteristics of the leaders of farmer group organizations Sinergy Tani this organization seems to be dominated by organizational leaders. Leaders are dominant in decision making. In the Harapan Gumanti Farmer Group organization, leaders maintain transparency to build member trust. The performance of the Sinergy Tani organization has made various efforts so that it can cultivate farming businesses to remain stable. Meanwhile, the Harapan Gumanti farmer group organization divides the work in shifts starting from the processing of land, planting to harvest time.